2011
DOI: 10.2499/9780896291812
|View full text |Cite
|
Sign up to set email alerts
|

Working multisectorally in nutrition Principles, practices, and case studies

Abstract: 1975 to identify and analyze alternative national and international strategies and policies for meeting food needs of the developing world on a sustainable basis, with particular emphasis on low-income countries and on the poorer groups in those countries. While the research effort is geared to the precise objective of contributing to the reduction of hunger and malnutrition, the factors involved are many and wide-ranging, requiring analysis of underlying processes and extending beyond a narrowly defined food … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…Several opportunities exist across countries for influencing policy formulation. Individual leadership 19,20,22 was seen as an important driver of policy influence and change in India and Pakistan-whether within government or by champions outside the government who have constructive relations with policy makers. Furthermore, particularly in India and Pakistan, issues that are more likely to win elections and give policy makers recognition are perceived to be prioritized, such as construction and infrastructure or electricity, as well as personal incentives related to financial benefits, job creation, or family.…”
Section: Political and Institutional Context Of Agriculture And Nutrimentioning
confidence: 99%
“…Several opportunities exist across countries for influencing policy formulation. Individual leadership 19,20,22 was seen as an important driver of policy influence and change in India and Pakistan-whether within government or by champions outside the government who have constructive relations with policy makers. Furthermore, particularly in India and Pakistan, issues that are more likely to win elections and give policy makers recognition are perceived to be prioritized, such as construction and infrastructure or electricity, as well as personal incentives related to financial benefits, job creation, or family.…”
Section: Political and Institutional Context Of Agriculture And Nutrimentioning
confidence: 99%
“…In fact, as demonstrated by the UNICEF framework, malnutrition is determined by a range of factors relying on the implementation of interventions by a multitude of sectors [3]. This multisectoral approach has resurged recently, given the rising of more favorable conditions for initiating projects [4,5]. Likewise, country assessments of nutrition problems are increasingly involving more and different sectors and a growing body of evidence is available about what works or not for improving nutritional status of populations.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, country assessments of nutrition problems are increasingly involving more and different sectors and a growing body of evidence is available about what works or not for improving nutritional status of populations. At the country level, governments and development partners are looking to determine where the problem lie and its causes to develop appropriate multisectoral strategies and programs to ensure optimal impact on the nutritional status of vulnerable populations [5].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the literature pertaining to nutrition governance is based in qualitative interviews with key informants and/or desk reviews of the presence/absence of key policy documents and legislation that would be supportive of national nutrition goals. 12,13 There have been few attempts to establish more quantifiable metrics that could be compared across country situations or monitored over time. [13][14][15] In their review of the state of evidence on processes that underpin political and policy successes for nutrition, Gillespie et al concluded that "analyses about how to shape and sustain enabling environments is essential, " and that "the collection of credible metrics … is desperately needed in this area. "…”
Section: Key Messagesmentioning
confidence: 99%
“…12,13 There have been few attempts to establish more quantifiable metrics that could be compared across country situations or monitored over time. [13][14][15] In their review of the state of evidence on processes that underpin political and policy successes for nutrition, Gillespie et al concluded that "analyses about how to shape and sustain enabling environments is essential, " and that "the collection of credible metrics … is desperately needed in this area. " 6 There is a need for a multisectoral approach to ensure delivery of nutrition-specific and sensitive actions to achieve and support nutrition goals.…”
Section: Key Messagesmentioning
confidence: 99%